Protocol data management in biology laboratories: proposal for developing a system - Aguiar Campos, Alessandra Conceição Faria (2020)
Organizing information objective is to disseminate the information objects effectively to the users. It is a complex but important task that uses elements such as the form and informational content of documents. Organized information is a prerequisite for an efficient organization. The goal of this study is to discuss the proposal of developing a system to organize protocol information from biological laboratories capable of managing protocol data. Research laboratories are examples of organizations that have a diverse and complex set of data that must be well organized. Their flow of information needs to be mapped identifying people, information sources, technology used as well as products and services. In this paper we describe the development of the FluxP system to organize information on protocols from a Biology Research Laboratory — The Animal Venoms and Toxins Laboratory (LVTA) from Federal University of Minas Gerais – Brazil. The following methodological procedures were adopted: technical visits, construction of a tool to manage the protocols (FluxP forms), categorization of the protocols used in the LVTA and experimental tests with 3 LVTA researchers. As a result, we highlight some features like: FluxP is able to manage protocol data making it simple to store and retrieve protocols to aid in the experimental work, increasing the reliability of experiments and helping reduce experimental errors.  By establishing a central repository for protocols FluxP prevents protocols from being misplaced or lost and by categorizing them it makes simple to retrieve protocols based on keywords.  The system is currently being used by LVTA to manage a collection of 50 protocols, and can be easily adapted for other laboratories.